Effect of Environmental High Temperature on the Reproductive activity of Awassi Ram Lambs - Kashef Al-Ghetaa, Hassan Falah (The Iraqi Journal of Veterinary Medicine, 2012)
The aim of this study was to detect the influence of high temperature during summer and early autumn seasons on the reproductive activity of Awassi ram lambs. Study conducted in Baghdad from June 1st 2011 to Nov. 30th 2011, using thirty Awassi ram lambs aged 11.5±1.5 months. Testis, Seminal vesicle gland and bulbourethral gland dimensions and weights were taken once monthly, cortisol and testosterone hormones were estimated, percentages of dead and abnormal sperms were calculated and histopathological examination was applied on the testes. The results revealed a significant (P<0.05) effects of hot season on the genital organ dimensions and weight, and on testicular histological texture leading to sloughing and degenerative changes in seminiferous tubules which causes elevating significantly (P<0.05) in percents of abnormal and dead sperms during mid-summer in comparison with fall season. There was decline in testosterone hormone level, while the cortisol hormone levels remains without significant differences. In conclusion: Awassi ram has a great ability to heat stress adaptation to decline the effect of external hyperthermia on reproductive ability as soon as possible, and can resume almost a perfect sexual activity with high fertility rate immediately at the regression of climatic high temperature.